The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/feart.2021.630469
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological Controls on Water Table Dynamics in Fen Peatlands Depend on Management Regimes

Abstract: Fens belong to the most threatened ecosystems in Europe. Maintaining a high water table through rewetting is an effective measure to rehabilitate many of their ecosystem functions. However, the impact of meteorological conditions such as vapor pressure deficit (VPD) and precipitation on water tables is still unclear for rewetted fens. Here, we compare the impact of meteorological factors on water table dynamics in a drained and a rewetted fen, using multiple regression with data from continuous high-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…Biodiversity loss is a critical threat, and preserving natural habitats, expanding protected areas, and restoring the degraded landscapes are crucial steps in biodiversity improvement. If the authors' findings [2] are followed, it becomes evident that the current consumption of land and resources by humans, alongside the corresponding environmental changes, has a predominantly negative impact on biodiversity at all levels, ranging from genetic diversity Land 2024, 13, 581 2 of 29 to the biome. Reintroducing degraded lands into new green infrastructures for urban areas [3,4], or areas close to the natural state habitats, is supported by ecological engineering approaches to reduce the land consumption pressures of built-up environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biodiversity loss is a critical threat, and preserving natural habitats, expanding protected areas, and restoring the degraded landscapes are crucial steps in biodiversity improvement. If the authors' findings [2] are followed, it becomes evident that the current consumption of land and resources by humans, alongside the corresponding environmental changes, has a predominantly negative impact on biodiversity at all levels, ranging from genetic diversity Land 2024, 13, 581 2 of 29 to the biome. Reintroducing degraded lands into new green infrastructures for urban areas [3,4], or areas close to the natural state habitats, is supported by ecological engineering approaches to reduce the land consumption pressures of built-up environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, intact peatlands mitigate the effects of global warming by manipulating the water cycle in two ways. According to Ahmad, Liu, and Alam et al [13], there is a connection between the meteorological influences, the groundwater level, and the latent heat flow. This comparison between a drained and a rewetted moor (same area) showed that on the one hand, the groundwater fluctuations were less pronounced; therefore, the daily evaporation for the rewetted moor could be increased by around 2.5 times.…”
Section: Introductionmentioning
confidence: 99%
“…The depth to water table in peatlands is not homogeneous and depends on spatial location (Joris & Feyen, 2003), soil physical parameters (Ahmad et al, 2021), vegetation cover (Volik et al, 2020), and of course seasonal atmospheric forcings. As a consequence, its effect on the concentrations of chemical elements varies both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
“…Although chloride behaviour is affected by several processes that indicate topsoil transformation, the depth to water table remains a crucial factor for the chloride concentrations in shallow groundwater. The depth to water table in peatlands is not homogeneous and depends on spatial location (Joris & Feyen, 2003), soil physical parameters (Ahmad et al, 2021), vegetation cover (Volik et al, 2020), and of course seasonal atmospheric forcings. As a consequence, its effect on the concentrations of chemical elements varies both spatially and temporally.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the importance of these near‐surface controls on peatland hydrology and carbon sequestration, historically the quantification of peatland hydrophysical properties and the hydrological simulation of the ecosystems has focused on peat properties at depth (Wang et al, 2021), linking surface ecological dynamics with the water table depth (WTD) (Ahmad et al, 2021). However, more recently, notably Canadian, peatland studies evaluated moss moistures stresses via known ecohydrological thresholds by quantifying bulk densities, hydrophysical properties, water table depths and peat moistures of very near‐surface layers regrowing or recolonizing onto the cutover surface (Cagampan & Waddington, 2008; Gauthier et al, 2018; Golubev et al, 2021; McCarter & Price, 2015; Turetsky et al, 2008; Waddington et al, 2011) This focus on near‐surface properties and hydrological dynamics is important.…”
Section: Introductionmentioning
confidence: 99%